2018
DOI: 10.1111/ppl.12762
|View full text |Cite
|
Sign up to set email alerts
|

Petunia as model for elucidating adventitious root formation and mycorrhizal symbiosis: at the nexus of physiology, genetics, microbiology and horticulture

Abstract: Adventitious root formation in cuttings and establishment of arbuscular mycorrhizal symbiosis reflect the enormous plasticity of plants and are key factors in the efficient and sustainable clonal propagation and production of ornamental crops. Based on the high importance of Petunia hybrida for the European and US annual bedding plant markets and its suitability as a model for basic plant sciences, petunia has been established as an experimental system for elucidating the molecular and physiological processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Depending on the status of the AR source cells, they can be directly fate-converted to AR root founder cells by a rootinducing signal or they first have to acquire root competence involving dedifferentiation . The natural ability of plants to regenerate is widely used in tissue culture, modern horticulture, and agriculture (Sussex, 2008;Druege and Franken, 2019). In rice and other cereals, ARs represent the main components of the root system as the primary root originating from the embryonic RAM is short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the status of the AR source cells, they can be directly fate-converted to AR root founder cells by a rootinducing signal or they first have to acquire root competence involving dedifferentiation . The natural ability of plants to regenerate is widely used in tissue culture, modern horticulture, and agriculture (Sussex, 2008;Druege and Franken, 2019). In rice and other cereals, ARs represent the main components of the root system as the primary root originating from the embryonic RAM is short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…JAs serve as a wound signal during AR formation, and they can be accumulated in plant tissues just a few minutes after wounding. It has been proposed that increased JA concentration promotes the formation of ARs in cuttings through accumulation of IAA in the base of stems and/or canalization towards AR source cells 4 . Felten et al (2010) 51 suggested that JA might act a molecular signal for inducing lateral roots.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of ARs is a complex process, which can be affected by multiple factors including genetics, age, endogenous hormones, and nutritional status of plants or plant organs to be used for cutting, as well as rooting environments, such as temperature, light, relative humidity, soil or substrate properties, and soil microbes 5,6 . Thus far, how plant endogenous clues interact with environmental factors in inducing AR formation is still poorly understood even though significant progress in molecular basis on AR formation has been made recently 4,7 . Natural auxin, indole-3-acetic acid (IAA) plays fundamental roles in AR formation 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations